Facile hydrothermal method for synthesizing nitrogen-doped graphene nanoplatelets using aqueous ammonia: dispersion, stability in solvents and thermophysical performances - Shazali, Siti Shafiah; Amiri, Ahmad; Zubir, Mohd Nashrul Mohd; Rozali, Shaifulazuar; Zabri, Mohd Zakuan; Sabri, Mohd Faizul Mohd (IOP Publishing, 2018)
A simple and green approach has been developed to synthesize nitrogen-doped graphene nanoplatelets (N-doped GNPs) for mass production with a very high stability in different solvents e.g. water, ethylene glycol, methanol, ethanol, and 1-hexanol. The strategy is based on mild oxidation of GNPs using hydrogen peroxide and doping with nitrogen using hydrothermal process. The modification of N-doped GNPs was demonstrated by FTIR, TGA, XPS, Raman spectroscopy and high resolution-transmission electron microscope (HRTEM). Further study was carried out by using N-doped GNPs as an additive to prepare different colloidal dispersions. Water-based N-doped GNPs, methanol-based N-doped GNPs, ethanol-based N-doped GNPs, ethylene-glycol based N-doped GNPs and 1-hexanol-based N-doped GNPs dispersions at 0.01 wt.% shown great colloidal stabilities, indicating 17%, 29%, 33%, 18%, and 43% sedimentations after a 15-days period, respectively. The thermophysical properties e.g., viscosity and thermal conductivity of water-based N-doped GNP nanofluids were also evaluated for different weight concentrations of 0.100, 0.075, 0.050, and 0.025 wt.%. Through this, it is found that the obtained dispersions have great potential to be used as working fluids for industrial thermal systems.